Avaliação de doenças ocupacionais relacionada as atividades do carteiro - Freitas, Johnys (2012)
The pains and illnesses, besides bringing losses in the Professional, also affect the quality of life of the employee, resulting in personal injury, and the burden that taxes are postmen and postures adopted by them at work can contribute to the onset of pain and illnesses. This paper aims to present a list of activities Postman in his routine and probable occupational diseases that may harm your health cause and removal service. And also sought to clarify why the overhead of correspondence is so great, because, is a fact that says the company respects because there is an impasse in hiring staff. Were observed and evaluated in person motorized Postmen, cyclists and pedestrians, to have a vision of what the differences of activities and mainly observe the movements that are inside and outside the distribution unit into your routine relating to the likely cause of occupational diseases. For had the legal foundation of the diseases from the wrongdoing and bad working practices repetitive movements used to Standards Regulatory pointing to factors that could be contributing to the emergence of diseases, where it was found that there is a need of furniture dimensioning and adaptation work. For this it was necessary to consult the NR 17 that comes to ergonomics and NR 15 on Unhealthy Activities and Operations. It was found through consultations electronically and in most magazines and books that the most common diseases in Postmen are the RSI (Repetitive Strain Injury) and WMSD (Work-Related Musculoskeletal Disorders), not to mention that many accidents occur in distribution activities leading to the expulsion of workers It is considered that it is necessary a greater concern with the performance of workers and Specialized Services in Safety and Occupational medicine in partnership with the Commission for the Prevention of Accidents CIPA that seeks to warn employees about such diseases and to study the internal conditions of work when it comes to light temperature, air humidity and sizing of furniture.